Wokół etyki niesienia pomocy psychologiczno-pedagogicznej - Dudek, Mieczysław (Annales. Etyka w Życiu Gospodarczym, 2008)
The most basic aim of the psychological and pedagogical advisory centre is providing the child and its family with support at every stage of the problems arising. The target of such centres is also undertaking preventive, diagnostic, therapeutic, counselling and advisory actions. The profession of a diagnostic – therapeutic counsellor triggers ethical dilemma. Two parties meet and interact with each other in the relations occurring in such advisory centres – the counsellor and the person who needs advice and help. To enable such a contact and make it effectively therapeutic instead of destructive, specialists employed in these centres have to be not only competent and highly qualified but also should possess a sufficient amount of knowledge about themselves, their system of values, opinions etc.